Investigation of machining performance of coated alumina cutting tool insert with sand blasting surface pretreatment - Mohd Azrulnizam, Abd. Aziz (2012)
The sand blasting process had been used as a process of surface pretreatment for the alumina cutting tool. The cutting tool insert were received as amorphous graphite deposited by using PVD technique. Machining workpiece was conducted on Ti alloy. Morphological observation by metallurgical microscope, the optical measurement has been used for observing the effect of flank wear and for surface roughness, the perthometer had been used in order to investigate the effect of surface pretreatment. The results show that alumina with PVD coated and sand blasting surface pretreatment had lower flank wear compare with alumina uncoated (as received) and alumina with only PVD coated. The surface roughness of alumina with sand blasting surface pretreatment are higher than as received cutting tool. The surface roughness of coated alumina with surface pretreatment is 0.634 nm higher than coated alumina without surface pretreatment which is 0.617 nm after machining process.The improvements of the alumina oxide affect their properties and cutting tool performance. The pretreatment with coated cutting tools give higher results in wear resistance compared to non-pretreatment and as received.